Autumn : the city - Moody, David, 1970- (St. Martin's Griffin, 2011)
"A disease of unimaginable ferocity has torn across the face of the planet, leaving billions dead. A small group of survivors shelter in the remains of a devastated city, hiding in terror as the full effects of the horrific infection start to become clear. The sudden appearance of a company of soldiers again threatens the survivors' fragile existence. Do they bring with them hope, help, and answers, or more pain, fear, and suffering?"--P. [4] of cover.